------------------------------------------------------------------------------------------
Equation
------------------------------------------------------------------------------------------
y = -3x - 9
------------------------------------------------------------------------------------------
Option 1
------------------------------------------------------------------------------------------
If I substitute x = -9, I should get y = 0
When x = -9
y = -3 (-9) - 9
= 18 (I did not get 0, wrong)
------------------------------------------------------------------------------------------
Option 2
------------------------------------------------------------------------------------------
If I substitute x = -3, I should get y = 0
y = -3(-3) - 9
y = 9 - 9
y = 0 (Yes, I got 0, correct)
------------------------------------------------------------------------------------------
Option 3
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -3
y = -3 (0) - 9
y = 0 - 9
y = -9 (I did not get -3, wrong)
------------------------------------------------------------------------------------------
Option 4
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -9
y = -3 (0) - 9
y = 0 - 9
y = -9 (Yes, I got -9, correct)
------------------------------------------------------------------------------------------
Answer: (-3, 0) and (0, 9) are ordered pairs of the equation (Answer B, D)
------------------------------------------------------------------------------------------
Answer:
D
Step-by-step explanation:
the triangle has reflected across either x-axis or p-axis. If across x-axis, the triangle needs to translate left and then up (no option for this).
Step-by-step explanation:
use herons formula
√s(s-a)(s-b)(s-c)
where s is the semi perimeter
S=20
and a,b,c are sides of triangle
=√20(20-17)(20-9)(20-14)
=√20.3.11.6
=62.92
nearest whole number is 63
option B is correct
Answer:
1/4x (8 x - 15)
Step-by-step explanation:
write the division as a fraction
1/2x + 3/2x (x - 5 ÷ 2)
factor out 1/2 from the expression.
1/2x(x + 3(x - 5 ÷ 2))
divide the numbers.
1/2x(x + 3(x - 2.5))
distribute 3 through the parentheses.
1/2x(x + 3x - 7.5)
collect like terms.
1/2x(4x - 7.5)
1/2x(4x - 15/2)
factor out 1/2 from the expression.
1/2 x 1/2 x (8 x - 15)
multiply the fractions
= 1/4 x (8x - 15)
or alternative form
= 0.25(8x - 15)